Access, participation and capabilities: theorising the contribution of university bursaries to students' well-being, flourishing and success. Issue 6 (2nd November 2018) - Harrison, Neil; Davies, Sara; Harris, Richard; Waller, Richard
Abstract: For the last 10 years, universities in England have been expected to offer financial support to low-income students alongside that provided by government. These bursaries were initially conceived in terms of improving access for under-represented groups, but attention has turned to their role in supporting student retention and success. This paper reports on two qualitative studies undertaken by contrasting universities that have been brought together due to their complementary findings. Semi-structured interviews were undertaken with a total of 98 students. Students' views on bursaries and how they impact on their lives are reported and used to develop a descriptive model of the web of choices that students have in balancing finances and time. This is contextualised within Sen's 'capabilities approach', to argue that providing access to higher education is insufficient if disadvantaged students are not able to flourish by participating fully in the university experience.